Probing Interfacial Nanostructures of Electrochemical Energy Storage Systems by In-Situ Transmission Electron Microscopy - Liang, Guisheng; Zhang, Chang; Yang, Liting; Liu, Yihao; Liu, Minmin; Xiong, Xuhui; Yang, Chendi; Lv, Xiaowei; You, Wenbin; Pei, Ke; Zhong, Chuan‑Jian; Cheng, Han‑Wen; et al. (Nano-Micro Letters, 2025)
The ability to control the electrode interfaces in an electrochemical energy storage system is essential for achieving the desired electrochemical performance. However, achieving this ability requires an in-depth understanding of the detailed interfacial nanostructures of the electrode under electrochemical operating conditions. In-situ transmission electron microscopy (TEM) is one of the most powerful techniques for revealing electrochemical energy storage mechanisms with high spatiotemporal resolution and high sensitivity in complex electrochemical environments. These attributes play a unique role in understanding how ion transport inside electrode nanomaterials and across interfaces under the dynamic conditions within working batteries. This review aims to gain an in-depth insight into the latest developments of in-situ TEM imaging techniques for probing the interfacial nanostructures of electrochemical energy storage systems, including atomic-scale structural imaging, strain field imaging, electron holography, and integrated differential phase contrast imaging. Significant examples will be described to highlight the fundamental understanding of atomic-scale and nanoscale mechanisms from employing state-of-the-art imaging techniques to visualize structural evolution, ionic valence state changes, and strain mapping, ion transport dynamics. The review concludes by providing a perspective discussion of future directions of the development and application of in-situ TEM techniques in the field of electrochemical energy storage systems. Highlights: 1 An in-depth look into the latest developments of in-situ transmission electron microscopy (TEM) imaging techniques for probing the interfacial nanostructures of electrochemical energy storage systems. 2 Selected examples to highlight the fundamental understanding of atomic-scale and nanoscale mechanisms by employing some of the state-of-the-art imaging techniques to visualize the interfacial nanostructural evolution. 3 The challenges and future directions of the development and application of in-situ TEM techniques in the cutting-edge areas of electrochemical energy storage research are discussed.